المصطلح النحوي في آثار محمد بن يوسف أطفيش - جلايلي, أحمد (University of Eloued جامعة الوادي, 2005)
يعالج هـذا الموضـوع رصـد المصطلحات اللغوية التي وظفها محمد ابن يوسف أطفيش في مؤلفاته . ولا يتناول البحث ضبط كل المصطلحات فكتاب " تيسير التفسيـر" لأطفيش ثَرِيٌّ بالتعـابير المتنوّعة، وبخـاصة التعابير البلاغية، التي عَدَلْنا عنهـا تاركينها لدارسـي البلاغة والنقد الأدبي. وممـا يخلص إليه البحث أن محمد بن يوسف أطفيش وظـف مصطلحات النحاة جميعهم بصريين وكوفيين، دون أن يلتزم بمدرسة معيّنة، وإن كان ميالا في أغلب الأحيـان إلى البصريين، لشيوع مصطلحاتهم وتداولها مشافهة وتأليفًا. This article treats the most important linguistic terms used by ‘Mohamed Ben Youcef Atfiche’. In his book “ TAYSIR EL TAFSIR”, one sees that it is full of various expressions especially the eloquent expressions which the author has left for the examiners of the eloquency and the literary critics. This research comes up with the idea that ‘Mohamed Ben Youcef Atfiche’ has used the terms of the grammarians of both El Basra and El Koufa without conforming himself with a specific school, even he deviates most of the times to El Basra school for their widespread terms used orally and in compose.
مقال بمجلة البحوث والدراسات
Keywords: مصطلح نحوي - مصطلح لغوي - محمد بن يوسف أطفيش